Development of integrated home security automation system / Muhammad Ruzaini Nordin and Mohd Rofdzi Abdullah - Nordin, Muhammad Ruzaini; Abdullah, Mohd Rofdzi (2019)
Building Information Modelling (BIM) is a methodology that influences data to analyze and predict outcomes through different phase of a building lifecycle. It helps in terms of facilitating the delivery of building information to the building stakeholders. In today's modernisation era, the emergence of the Building Automation System (BAS) gives a significant impact on the lifecycle of building by introducing a new way of energy usage management in a building. As a new technological system, BAS obviously has its challenges in implementation and management. Hence, the paper objectives are to identify the challenges in building management of BAS and determine how BIM can contribute to the growth of BAS and to integrate both platforms for increased building lifecycle efficiency. By integrating both platforms using a visual programming interface as the principle method, it can be deduced to overcome the issues of BAS by accessing the same data as in the BAS control panel but in an easier working and customisation interface and comprehensive detailing. Therefore, contribute towards more sustainability and efficiency of built environment energy management.